The genus Radula (Radulaceae, Marchantiophyta) in Andaman & Nicobar Islands, India. (2nd July 2016) - Singh, D. K.; Dey, Monalisa; Singh, Devendra
Abstract : The genus Radula Dumort. has been investigated in the Indian Union Territory of Andaman & Nicobar in the Bay of Bengal and twelve species have been found to occur in these islands. Of these, R. nymanii Steph. is new to the Indian bryoflora from the Nicobar Islands. The occurrence of R. anceps Sande Lac. in the country is confirmed. R. acuminata Steph., R. auriculata Steph., R. fulvifolia (Hook.f. & Taylor) Gottsche, R. perrottetii Gottsche ex Steph., R. protensa Lindenb., R. sumatrana Steph. and R. tjibodensis K.I.Goebel, until now only known in the Indian bryoflora from mainland, have been recorded for the first time on these islands. Detailed descriptions and illustrations are provided for R. anceps, R. nymanii and R. sumatrana, based on Indian materials, to facilitate their easy identification. These discoveries suggest that the liverwort flora of Andaman & Nicobar is grossly understudied. The earlier reports of R. campanigera Mont., R. tenerrima Steph. and R. vrieseana Sande Lac. from these islands are considered to be doubtful. R. kurzii is known only from the South Andaman, while R. javanica is the most extensively distributed species in this territory occurring in several areas of both Andaman as well as the Nicobar group of islands. All other species are presently known from the Nicobar Islands only. The Radula flora of Andaman & Nicobar Islands shows a close affinity with that of mainland India, China and Indonesia.